Stress Distribution and Failure Characteristics of Stope Overburden of an Inclined Coal Seam. (8th December 2021) - Liu, Xin; Sun, Jian; Yang, Yong
Abstract : The stress distribution, failure depth, and shape and range of overlying strata of the stope are important bases for the prevention of roof water hazards and determination of reasonable locations of roof roadways. Based on the hydrogeological data of the E9103 workface, FLAC numerical simulation software was used to establish a numerical calculation model of the overlying strata of the E9103 inclined coal seam, and the stress distribution and failure characteristics of the overlying strata were analyzed. The development height of the caving and water-flowing fractured zones in the overlying strata of the workface was determined. Results showed that the stress reduction area appeared above the goaf in the form of an "arched" distribution, and tensile stress occurred in the local area of the overburden. The overburden relief arch of the workface was symmetrically distributed along the advanced direction and asymmetrically distributed along the inclined direction, with the arch crown deflecting above the workface. The horizontal and vertical displacements of the overlying strata of the stope increased with the advancing distance of the workface. The horizontal displacement in the x -direction presented two obvious regions, and the critical points of the two regions moved forward with the advancement of the workface and showed a certain degree of symmetry. The horizontal displacement in the y -direction presented an "inverted bowl" distribution and increased with the advancement of the workface. The main failure forms of the overlying strata of the workface were a tensile and shear failure, and shear failure was dominant in the upper direction. The height of the overburden caving zone in the workface had little relationship with the advancing distance of the workface and increased slowly as the advancing distance of the workface increased. The development height of the caving zone is 7.2–18.13 m. The development height of the water conduction fissure zone increased rapidly with the increase in the advancing distance of the workface. When the advancing distance was equal to the length of the workface, the development height of the water conduction fissure zone was flat and basically maintained at a stable value. The development height of the water conduction fissure zone is 30.8–62.2 m. These research findings have important engineering importance for ensuring safe and efficient mining of E9103 workface.